Are small bore thorax catheters effective in the treatment of primary spontaneous pneumothorax? - Balta, Cenk; Karacaoğlu, İsmail and Mergan, Duygu and Yekdeş, Ali Cem (Journal of Surgery and Medicine, 2020)
Aim: The first option in the treatment of primary spontaneous pneumothorax (PSP) is still controversial. Large bore thoracic drains (LBTD) are generally preferred by clinicians. However, the use of small-bore thorax catheters (SBTC) has increased in recent years. In our study, we aimed to compare the treatment efficacy, clinical outcomes and pain levels of small and large diameter thoracic catheters used in PSP treatment. Methods: Patients over the age of 18 who presented with a diagnosis of PSP between August 2017 and August 2019 were included in the study. The patients were divided into two groups according to the application of small and large bore thorax drain. Demographic information, clinical results and pain levels of the groups were analyzed retrospectively. The duration of hospitalization, duration of drainage and Visual Analogue Scale (VAS) results were evaluated comparatively. Results: 95 male and 10 female patients with a median age of 26 (22-33) were included in the study. LBTD was applied to 47 (44.8%) and SBTC was applied to 58 (55.2%) of the patients. Recurrence was observed in 6 (12.8%) of LBTD group and in 4 (6.9%) SBTC group. VAS scores, drainage time, hospital stay were significantly less in patients with small-sized drainage. Conclusion: SBTC application is easy to apply, causes less pain, has shorter drainage time and duration of hospital stay. It is as effective as traditional thoracic drains in the treatment of PSP.